- Uji Efektivitas Ekstrak Bunga Pepaya (Carrica papaya L.) Terhadap Kadar Gula Darah Mencit (Mus musculus L.) Jantan Yang Diinduksi Sukrosa: Uji Efetivitas Ekstrak Bunga Pepaya (Carrica Papaya L.) Terhadap Kadar Gula Darah Mencit (Mus Musculus L.) Jantan Yang Diinduksi Sukrosa - Marpaung, Febri Sri; Tampubolon, Ester Juanita br.; Andika, Muhammad Insan; Lubis, Yolanda Eliza Putri; Mutia, Maya Sari (Universitas Jambi, 2021)
The papaya (Carica papaya L) flower contain flavonoids, tannins, and triterpenoid steroids which function as antidiabetic. This study was conducted to determine the antidiabetic effect of papaya (Carica papaya L) flower extract on sucrose-induced male mice. In this study, mice were made diabetic by inducing them with sucrose at a dose of 160 mg/kg BW. A total of 25 mice were grouped homogeneously into 5 groups, consisting of a negative control group (CMC 0.5%), a positive control group (no administration), a group with a dose of 200 mg/kg BW, a group with a dose of 400 mg/Kg. BW, and the group with a dose of 500 mg/Kg BW. Measurement of blood sugar levels of mice was carried out before administration of sucrose, after administration of sucrose and after administration of papaya flower extract. The results showed that the three doses had an antidiabetic effect, and the administration of papaya flower extract at a dose of 200 mg/Kg BW showed a better effect than the negative control.